2015
DOI: 10.4132/jptm.2015.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Cancers with Higher Density of Tumor-Associated Macrophages Were Associated with Poor Survival Rates

Abstract: Background:Macrophages are a component of a tumor’s microenvironment and have various roles in tumor progression and metastasis. This study evaluated the relationships between tumor-associated macrophage (TAM) density and clinical outcomes in 14 different types of human cancers.Methods:We investigated TAM density in human tissue microarray sections from 14 different types of human cancers (n = 266) and normal thyroid, lung, and breast tissues (n = 22). The five-year survival rates of each cancer were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 27 publications
4
127
1
1
Order By: Relevance
“…Since the last decade, many studies have demonstrated that the density of TAMs is associated with a poor prognosis, suggesting macrophages as a target for clinical therapy [49][50][51][52][53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…Since the last decade, many studies have demonstrated that the density of TAMs is associated with a poor prognosis, suggesting macrophages as a target for clinical therapy [49][50][51][52][53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…63,54 A myriad of immune cells are present in the TC microenvironment and in some cases are associated with patient outcome. 66,68 However, only studies assessing the functional role of TAMs and TAMCs in the TC microenvironment have provided evidence for their protumorigenic role. 14,24 The majority of these studies were merely qualitative and quantitative analyses of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…66 In PTCs, TAMs correlated with lymphnode metastasis, 45 larger tumor size 67 and reduced survival. 68 In PDTC, TAM density correlates with capsular invasion and extrathyroid extension. 66 TAMs represent more than 50% of immune cells in ATCs forming a "microglia-like" in close contact with cancer cells.…”
Section: Immune Cells In Tc Microenvironmentmentioning
confidence: 99%
“…In particular, anaplastic thyroid cancers were found to have the most TAMs, with their 24:12 numbers correlating with poorer prognoses (Jung et al 2015). Although the average number of TAMs tends to be lower in papillary thyroid cancers, there is a similar correlation with clinical outcomes, including more lymph node metastases, larger tumors and reduced survival (Ryder et al 2009, Fang et al 2014, Jung et al 2015. In vitro data also suggested that TAMs could promote invasiveness of a human thyroid cancer cell line through interleukin (IL)-8 secretion (Fang et al 2014).…”
Section: Myeloid Cellsmentioning
confidence: 99%
“…The density of tumor-associated macrophages (TAMs) varies in the different pathologic subtypes of thyroid cancers (Jung et al 2015). In particular, anaplastic thyroid cancers were found to have the most TAMs, with their 24:12 numbers correlating with poorer prognoses (Jung et al 2015).…”
Section: Myeloid Cellsmentioning
confidence: 99%